Part one. The preparation and structure of sucrose monoesters, and, Part two. The esterification of 1,4;3,6-dianhydro-D-glucitol . - McInnes, Alister Gavin. (University of Ottawa (Canada), 1961)
Abstract not available.
Keywords: Chemistry, Organic.